Simultaneous integrated boost for adjuvant treatment of breast cancer- intensity modulated vs. conventional radiotherapy: the IMRT-MC2 trial - Askoxylakis, Vasileios; Jensen, Alexandra; Häfner, Matthias; Rudofsky, Leonie; Sterzing, Florian; Heil, Jörg; Sohn, Christof; Hüsing, Johannes; Kraus-Tiefenbacher, Uta; Wenz, Frederik; Debus, Jürgen; Hof, Holger (BMC cancer, 2011)
Radiation therapy is an essential modality in the treatment of breast cancer. Addition of radiotherapy to surgery has significantly increased local control and survival rates of the disease. However, radiotherapy is also associated with side effects, such as tissue fibrosis or enhanced vascular morbidity. Modern radiotherapy strategies, such as intensity modulated radiotherapy (IMRT), can shorten the overall treatment time by integration of the additional tumor bed boost significantly. To what extent this might be possible without impairing treatment outcome and cosmetic results remains to be clarified.